Metafora Pengungkapan Panyandra Perilaku Baik dan Buruk pada Web Series Tilik Karya Wahyu Agung Prasetyo - Lestari, Sri Indah; Fateah, Nur; Miji Lestari, Prembayun (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines the metaphor of expressing panyandra in the behavioral and bad categories in the web series Tilik by Wahyu Agung Prasetyo. In addition to the web series using Javanese and having many viewers, the web series also contains many panyandra, using a cognitive semantic approach, data collection using the listening and noting technique from the WeTv application. The analysis was carried out to identify the types of metaphors according to Kerbrat Orecchiomi, reference sources, and reference targets. This study aims to explain the types of metaphors, reference sources, and reference targets. The findings of this study reveal the types of metaphors according to Kerbrat Orecchiomi, namely explicit metaphors (in praesentia) and implicit metaphors (in absentia), and describes the source (source domain) and target reference (target domain). Explicit metaphor (in praesentia) is a metaphor that contains explicit meaning, while implicit metaphor (in absentia) is a metaphor that contains implied meaning and must be interpreted more deeply. After being classified into metaphor types, then analyzed phrases containing metaphors through reference sources (source domain) and reference targets (target domain). The results of the study show that the types of metaphors according to Kerbrat Orecchiomi in this study there are five types of explicit metaphors and three types of implicit metaphors, then mapping the table of reference sources and reference targets aims to interpret the meaning of panyandra from the speaker to the interlocutor, whether it is in the form of praise, sarcasm, criticism, and blame. The implication of this study for the study of cognitive semantics is to broaden the understanding of the meaning of language, because the study of cognitive semantics helps understand the formation of language meaning that is processed through the human mind.